About family Apostol Fubini-Euler type polynomials: fourier expansions and integral representation (2024)
This paper introduces new families of Fubini-Euler type and Apostol Fubini-Euler type polynomials, providing expressions, recurrence relations, and identities. We also derive Fourier series, and integral representations, and present their rational argument representation.